Experimental Investigation of Parameters Impacting the Roughness of Pinus elliottii Wood - Leite, Sueli Souza [UNESP]; Kim Jesus, Gessica Mina [UNESP]; Sampaio Alves, Manoel Cleber de [UNESP]; Valarelli, Ivaldo de Domenico [UNESP]; Moizes, Fabio Alexandre [UNESP]; Salvadeo, Vitor Manoel [UNESP] (North Carolina State Univ Dept Wood & Paper Sci, 2019)
The wood sanding process entails a small reduction in the dimensions of the workpiece in the course of modifying its surface morphology, which affects the aesthetics and the subsequent application of a coating. However, sanding is costly, partly because it is performed empirically without standardization. Therefore, this study analyzed the influence of sandpaper factors on the behavior of wood surface roughness for Pinus elliottii. A complete factorial experiment was performed, varying two types of abrasives, aluminum oxide and silicon carbide, in three grit sizes (80, 100, and 120), and three sandpaper conditions (new, semi-new, and worn). The tests were performed using a flat sander with a pneumatic circuit and monitoring system for data acquisition, which were analyzed through multiple Tukey tests. The results were organized in a consultation table that compared the combination of factors analyzed, informing whether they produced roughness of the wood equal to or distinct from each other. The results showed that new aluminum oxide sandpapers with grit sizes of 80, 100, and 120 produced roughness of the wood different from each other, while the carbide did not. Therefore, there is no need to trade or buy silicon carbide sandpaper in these grit sizes.
Keywords: Factorial experiment; Wood sanding process; Surface roughness of wood